2016
DOI: 10.1002/pon.4093
|View full text |Cite
|
Sign up to set email alerts
|

Perceived diagnostic delay and cancer-related distress: a cross-sectional study of patients with colorectal cancer

Abstract: Perceived diagnostic delay was associated with higher cancer-related distress among CRC survivors. While poorer quality of life partly explained such associations, fear of cancer recurrence, stage at diagnosis and treatment did not. The exact features of diagnostic delay that are associated with cancer-related distress remain unclear. Future research should examine the experiences patients go through prior to diagnosis that may increase distress, in an effort to improve our understanding of the factors affecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 41 publications
2
31
0
Order By: Relevance
“…Findings from the study are also in alignment with the literature by indicating that fear about having a serious health condition is an important cause of anxiety among patients and family members waiting for diagnosis [27]. Also in accordance with the literature, findings showed that perceived long timelines add stress to an already stressful situation [28]. Consistent with previous research, participants associated delays with their inaction or late action in seeking medical attention [6], with their doctor's failure to correctly identify cancer symptoms [12,29], and with system inefficiencies including variable access to specialists and testing and limited coordination of care [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…Findings from the study are also in alignment with the literature by indicating that fear about having a serious health condition is an important cause of anxiety among patients and family members waiting for diagnosis [27]. Also in accordance with the literature, findings showed that perceived long timelines add stress to an already stressful situation [28]. Consistent with previous research, participants associated delays with their inaction or late action in seeking medical attention [6], with their doctor's failure to correctly identify cancer symptoms [12,29], and with system inefficiencies including variable access to specialists and testing and limited coordination of care [30,31].…”
Section: Discussionsupporting
confidence: 84%
“…Delays in time to treatment initiation (TTI) for new cancer diagnoses are commonly known to cause patient anxiety and distress [1, 2, 3, 4]. Physicians often reassure patients that current wait times to initiate therapy will not impact long-term outcomes, but the evidence is conflicting.…”
Section: Introductionmentioning
confidence: 99%
“…Heightening the fear of recurrence is an added concern that is particularly relevant to haematological cancer survivors, namely the difficulty in diagnosing their cancers. A study from the UK has shown that is not uncommon for the diagnosis period for haematological cancers to be long and protracted (Howell et al, ) and diagnostic delay has been shown to cause increased distress in other cancer patients (Miles et al, ; Risberg, Sørbye, Norum, & Wist, ). The concern regarding their prolonged diagnostic period was carried through to participants in the post‐treatment period and contributed to their increased self‐monitoring.…”
Section: Discussionmentioning
confidence: 99%